The influence of age and dosage on the pharmacodynamics of dexmedetomidine in rabbits - Bienert, Agnieszka; Płotek, Włodzimierz; Wiczling, Paweł; Warzybok, Justyna; Borowska, Katarzyna; Buda, Katarzyna; Kulińska, Karolina; Billert, Hanna; Kaliszan, Roman; Grześkowiak, Edmund (Journal of Medical Science, 2014)
Aim. This study aimed to examine the influence of maturation and dosage on the sedative and haemodynamic response observed in rabbits after the administration of dexmedetomidine. Material and methods. The pharmacodynamics of dexmedetomidine was studied on 14 healthy New Zealand white rabbits at three periods of maturation; stage 1–1.5 months old, stage 2–2.5 months old and stage 3–6.5 months old ones. The administered dose of dexmedetomidine ranged from 25 µg/kg to 300 µg/kg of body weight. The pedal withdrawal reflex was used to measure the duration of anaesthesia. The heart rate and mean arterial pressure were measured at the third stage of the study to evaluate the haemodynamic response. A simple pharmacodynamic relationship between the dose and the duration of anesthesia was used to describe the data. Results. We observed that young rabbits were less sensitive to dexmedetomidine than adult animals, as was reflected by the pedal withdrawal reflex, and we found that the haemodynamic response to dexmedetomidine depended on dosage of the drug. Dexmedetomidine decreased the mean blood pressure in a dosage-dependent manner with the highest decrease observed for the lowest dose. As the dose increased, the hypotensive effect of the drug was less noticeable. After the administration of dexmedetomidine the heart rate decreased to the same value regardless of the dose applied.